2015
DOI: 10.1063/1.4916391
|View full text |Cite
|
Sign up to set email alerts
|

A monomeric complex of ammonia and cuprous chloride: H3N⋯CuCl isolated and characterised by rotational spectroscopy and ab initio calculations

Abstract: The H3N⋯CuCl monomer has been generated and isolated in the gas phase through laser vaporisation of a copper sample in the presence of low concentrations of NH3 and CCl4 in argon. The resulting complex cools to a rotational temperature approaching 2 K during supersonic expansion of the gas sample and is characterised by broadband rotational spectroscopy between 7 and 18.5 GHz. The spectra of six isotopologues are measured and analysed to determine rotational, B0; centrifugal distortion, DJ, DJK; and nuclear qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Similar arguments to those presented above explain the absence of K 1 = 1 transitions for the partially deuterated isotopologues of NH 3 · · · AgI, an observation consistent with previous results obtained through studies of H 3 N· · · MX complexes. 12,13 C. Molecular geometry Figures 3 and 4, respectively, show the model geometries of the H 2 O· · · AgI and H 3 N· · · AgI complexes. Structural parameters in these models were directly fitted to moments of inertia using Kisiel's STRFIT program 41 to yield r 0 results.…”
Section: B Spectroscopic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar arguments to those presented above explain the absence of K 1 = 1 transitions for the partially deuterated isotopologues of NH 3 · · · AgI, an observation consistent with previous results obtained through studies of H 3 N· · · MX complexes. 12,13 C. Molecular geometry Figures 3 and 4, respectively, show the model geometries of the H 2 O· · · AgI and H 3 N· · · AgI complexes. Structural parameters in these models were directly fitted to moments of inertia using Kisiel's STRFIT program 41 to yield r 0 results.…”
Section: B Spectroscopic Analysismentioning
confidence: 99%
“…A very similar trend was observed in the equivalent L· · · CuCl series. 4,6,10,12 The variation in χ aa (Cl) provides an indication of the extent of electron redistribution accompanying the formation of each of these complexes. Evidently, stabilisation of OC· · · MCl through back-donation of electrons from d orbitals of the metal onto π* orbitals of CO leads to a stronger interaction than that existing within Ar· · · MCl.…”
Section: Introductionmentioning
confidence: 99%
“…eQq197 (Au) = −41.0(18) • eQq( 35 Cl) − 2501(96) MHz with an R 2 = 0.996 fits the data without the experimental H 2 -AuCl data and with this data becomes eQq 197 (Au) = −41.4(15) • eQq( 35 Cl) − 2529(75) MHz with an R 2 = 0.996.…”
mentioning
confidence: 61%
“…9 Unlike the coinage metal studies, these systems were found to have van der Waals interaction energies (≤18 kJ mol 1 ) 10 and larger Ar-M distances. More recently, Walker, Legon, and co-workers have investigated the MX interaction with both polar [11][12][13][14][15][16][17][18][19][20] and non-polar polyatomic molecules. [21][22][23] In all MX studies listed above, the nuclear quadrupole coupling constant (NQCC), or eQq, has served as a probe for the change in the electronic structure of the metal when present.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, following the original work on complexes Rg· · ·MX and OC· · ·MX (M = Cu, Ag, or Au; X = F, Cl, Br, or I) by Gerry and co-workers, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] we have been investigating systematically by rotational spectroscopy a wide range of complexes B· · ·MX involving another type of non-covalent interaction which links a coinage metal halide MX (M = Cu, Ag, or Au, X = F, Cl, or I) via the metal atom M to one of a number of small Lewis bases B (for example, B = N 2 , OC, NH 3 , HC≡ ≡CH, H 2 C= =CH 2 , (CH 2 ) 3 , H 2 O, and H 2 S). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In the more strongly bound of these complexes, the approximations that B is unchanged on complex formation and that the intermolecular stretching force constant k σ is very much smaller than all stretching constants of the same symmetry are not valid and in particular the order k σ ≪ k MX does not hold. In such circumstances, the Millen equations are only approximate; recent work indicates that the diatomic approximation gives better agreement with results calculated ab initio.…”
Section: Introductionmentioning
confidence: 99%